Débats médiatisés et numériques sur la sécheresse. Le cas des pénuries d’eau dans un climat semi-aride en Arizona - Anne-Lise Boyer; Brigitte Juanals; Jean-Luc Minel (Communiquer)
This article aims to analyze the publicization of debates on public policy orientations, sociotechnical choices, and alternative solutions proposed by stakeholders to address situations of drought and water scarcity. It takes the case study of the state of Arizona (USA), where these situations are becoming more frequent and severe. The analysis combines qualitative data from interviews and field observations with the analysis of actor networks, discourse collected from the local daily press and Twitter messages. It appears that political and economic positions have decisive consequences for the distribution of water resources. Lastly, the article demonstrates how statements and discourses, when linked to field surveys, represents a major source for assessing the spatiotemporal configurations of drought episodes and determining the risks and measures that are a cause for concern to societies and are, therefore, the subject of public debates.